African Swine Fever Virus Immunosuppression and Virulence-Related Gene - Tao Huang; Fangtao Li; Yingju Xia; Junjie Zhao; Yuanyuan Zhu; Yebing Liu; Yingjuan Qian; Xingqi Zou (Current Issues in Molecular Biology, 2024)
African swine fever virus (ASFV), a highly contagious pathogen characterized by a complex structure and a variety of immunosuppression proteins, causes hemorrhagic, acute, and aggressive infectious disease that severely injures the pork products and industry. However, there is no effective vaccine or treatment. The main reasons are not only the complex mechanisms that lead to immunosuppression but also the unknown functions of various proteins. This review summarizes the interaction between ASFV and the host immune system, along with the involvement of virulence-related genes and proteins, as well as the corresponding molecular mechanism of immunosuppression of ASFV, encompassing pathways such as cGAS-STING, nuclear factor kappa–light-chain-enhancer of activated B cells (NF-κB), Janus Kinase (JAK) and JAK Signal Transducers and Activators of Transcription (STAT), apoptosis, and other modulation. The aim is to summarize the dynamic process during ASFV infection and entry into the host cell, provide a rational insight into development of a vaccine, and provide a better clear knowledge of how ASFV impacts the host.